1976
DOI: 10.1080/03015521.1976.10425909
|View full text |Cite
|
Sign up to set email alerts
|

Long-term leaching of nutrients from magnesium ammonium phosphate at various temperatures

Abstract: Magnesium ammonium phosphate and iron-bearing magnesium ammonium phosphate (containing ferrous ammonium phosphate) were made in a pilot-plant, and pellets were prepared trom these products by bonding with 10% by weight of potassium sulphate. These rellets and a range of conventional water-soluble fertilisers were leached on soil columns for 3-6 months .at 23°c, 37°c, and 53°c. and the .leachates were analysed. Nitrogen, phosphorus, and magnesium leached slowly oyer long periods from the magnesium ammonium phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 5 publications
(4 reference statements)
0
15
0
Order By: Relevance
“…This biological process is dependent on temperature, other nutrients, oxygen and microbial community composition. Further experiments with nitrification inhibitors, sterile soil, and varying temperatures support the theory that nitrification of ammonia often limits struvite dissolution (Rothbaum & Rohde, 1976). In a fertile aerobic soil, ammonium can be converted to nitrate within days, whereas some anaerobic soils have permanently high ammonium levels in which case another process might be limiting dissolution.…”
Section: Solubility and The Behavior Of Struvite In Soilmentioning
confidence: 73%
“…This biological process is dependent on temperature, other nutrients, oxygen and microbial community composition. Further experiments with nitrification inhibitors, sterile soil, and varying temperatures support the theory that nitrification of ammonia often limits struvite dissolution (Rothbaum & Rohde, 1976). In a fertile aerobic soil, ammonium can be converted to nitrate within days, whereas some anaerobic soils have permanently high ammonium levels in which case another process might be limiting dissolution.…”
Section: Solubility and The Behavior Of Struvite In Soilmentioning
confidence: 73%
“…Rothbaum and Rohde (1976) suggested that struvite dissolution might be increased by an aerobic microbiological mineralization mechanism, though this finding has not subsequently been investigated. Mackay and Syers (1986) found that high Ca concentration in the soil solution inhibited the dissolution of Ca phosphate rock.…”
mentioning
confidence: 99%
“…Improved growth of grass, fruit and various high-value crops was observed when they were fertilized with struvite, compared with conventional soluble fertilizers (Rothbaum and Rohde, 1976). Its use may be particularly advantageous when soluble fertilizers are inefficient, low soluble salts are required in the root zone, or a long residual effect is required.…”
Section: Introductionmentioning
confidence: 99%